Wireless mobile communication and healthcare : Second international ICST conference, MobiHealth 2011, Kos Island, Greece, October 5-7, 2011. Revised Selected Papers - Nikita, Konstantina S. (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering,, 2012)
This book constitutes the refereed proceedings of the Second International ICST Conference on Wireless Mobile Communication and Healthcare, MobiHealth 2011, held on Kos Island, Greece, in October 2011. The 60 revised full papers presented were carefully reviewed and selected from more than 80 submissions. The papers are organized in 10 sessions and two workshops with topics covering intrabody communications, chronic disease monitoring and management, ambient assistive technologies, implantable and wearable sensors, emergency and disaster applications.